ETMR-04. EMBRYONAL TUMOR WITH MULTILAYERED ROSETTES: THE MD ANDERSON CANCER CENTER EXPERIENCE. (4th December 2020) - Gupta, Sumit; Ragoonanan, Dristhi; Itzep, Nelda; Sandberg, David; Fuller, Greg; Ketonen, Leena; Meador, Heather; Zaky, Wafik; Khatua, Soumen
Abstract: BACKGROUND: Embryonal Tumor with Multilayered Rosettes (ETMR) are rare tumors that are molecularly diagnosed by C19MC amplification. Rarity of this tumor has precluded profiling uniform therapeutic strategy. METHODS: Retrospective review after institutional approval, identified 10 pediatric case of ETMR, treated at MD Anderson Cancer Center during the period of 2005 to 2019. RESULTS: Median age of at diagnosis was 4.6 years. Tumor sites include frontal or parietal lobes (3), spine (3) and posterior fossa involving the brainstem (4). All patients received a combination of chemotherapy and radiation. 4 patients had metastasis at the presentation. 9 patients received focal radiation but only 6 of them received Craniospinal irradiation (CSI). Average dose of radiation was 50 Gy. Surgical resection was performed in all cases except the brainstem tumors. 7 children had recurrence including all the patients with metastasis at diagnosis (median time: 9.4 months), 1 passed away secondary to hemorrhage in brainstem and data was not available for 2 patients. 5/6 patients who received CSI had recurrence. CONCLUSIONS: To-date no well-defined treatment regimens exists for these neoplasms, resulting in poor overall survival. Preclinical drug screen have shown the efficacy of topotecan, actinomycin D, and volasertib as potential new therapeutic candidates, though this has not translated successfully into the clinical arena. Given the limited success with current conventional therapeutic methods, molecular interrogation in addition to histopathological diagnosis are essential upfront, as it could provide clues to targeted therapy. Defining molecularly-based treatment with less toxicities and increased survival are warranted.